El regreso de Martin Guerre - Davis, Natalie Zemon, 1928-; Guerre, Martin, active 1539-1560.; Du Tilh, Arnault, -1560.; Rotés, Helena, 1954-; Serna Alonso, Justo; Pons, Anaclet; Davis, Natalie Zemon, 1928- (Tres Cantos, Madrid, España : Ediciones Akal, S.A., 2013)
Tells the story of a sixteenth-century French imposter who convinced a peasant woman and her family that he was her missing husband.
Includes bibliographical references.
Online resource; title from ePub title page (Digitalia, viewed May 13, 2016)
Keywords: Du Tilh, Arnault, -- -1560 -- Trials, litigation, etc; Guerre, Martin, -- active 1539-1560.; Trials (Impostors and imposture) -- France; Impostors and imposture -- France; Electronic books